Pengaruh Perputaran Kas, Rasio Lancar, Total Asset Turnover, Dan Debt To Equity Ratio Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ardin Waruwu; Tetty Tiurma Uli Sipahutar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to examine the effect of cash turnover, current ratio, total asset turnover, and debt to equity ratio on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a population of 145 companies for the 2017-2019 period. The sample selection process used in this research is using purposive sampling method, with the acquisition of a sample of 75 companies. This research was conducted using multiple linear regression analysis method with SPSS 21 program. Based on the results of the research that has been done, it shows that simultaneously the variables of cash turnover, current ratio, total asset turnover and debt to equity ratio have a significant effect on profitability. Partially, it shows that the cash turnover and debt to equity ratio (DER) variables have no significant effect on profitability. While the current ratio variable has a significant positive effect on profitability, and total assets turn over (TATO) has a significant effect on profitability. Keywords: Cash Turnover, Current Ratio, Total Asset Turnover, Debt To Equity Ratio, Profitability